2022
DOI: 10.3390/healthcare10101821
|View full text |Cite
|
Sign up to set email alerts
|

How Physical Activity Affects Knee Cartilage and a Standard Intervention Procedure for an Exercise Program: A Systematic Review

Abstract: (1) Background: Cartilage degeneration with the natural aging process and the role of physical activity on cartilage wellness is still not clear. The objective of the present review was to understand how different physical activity interventions affect the cartilage and to propose a Standard Operating Procedure for an exercise program to maintain knee joint health; (2) Methods: Articles were collected on three different electronic databases and screened against the eligibility criteria. Results were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Data from several recent reports [ 36 , 85 , 86 ] portrayed COMP, MMPs, CTX-I, CTX-II, and IL-1b as valid biomarkers for OA. There is heterogeneity in the published studies on this topic, most likely due to the variable selection of biomarker panels [ 29 ]. This critical aspect highlights the importance of establishing: (1) the reliability of the chosen biomarkers, as well as (2) defining the most suitable panel of biomarkers for OA and cartilage health in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from several recent reports [ 36 , 85 , 86 ] portrayed COMP, MMPs, CTX-I, CTX-II, and IL-1b as valid biomarkers for OA. There is heterogeneity in the published studies on this topic, most likely due to the variable selection of biomarker panels [ 29 ]. This critical aspect highlights the importance of establishing: (1) the reliability of the chosen biomarkers, as well as (2) defining the most suitable panel of biomarkers for OA and cartilage health in general.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted over the years on OA biomarkers, identifying many options for evaluating its progression and severity; however, the literature has been widely heterogeneous when physical activity is an included variable. Considering the importance of regular physical activity for articular cartilage health, the broad heterogeneity of findings in published studies [ 29 ], and the importance of personalized protocols and treatments (especially for people with OA) [ 30 ], and also taking into account that it is fundamental to better understand the role of the intervention on cartilage health through an appropriate and comparable evaluation, it is consequently important to standardize the evaluation methods by adopting the same biomarkers, and for this reason, standard operating procedures are required [ 24 ]. Consequently, this review aims to narrow the evaluation of relevant articular cartilage biomarkers, with emphasis on those markers that can draw some benefits from physical activity, and eventually propose a standard operating procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Corroborating our findings, distinct studies have shown that older adults with KOA have impaired functional parameters. ( 6 , 13 , 14 , 15 , 34 , 35 )…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, strengthening training in combination with other types of exercises (e.g., functional exercise) significantly improved pain relief, physical function, and quality of life in KOA patients. ( 15 ) Pain has also eased after performing aerobic training, resistance training, or combined training in KOA patients. ( 16 )…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis (OA) is the most common knee-joint disease in middle-aged and elderly people [ 8 , 9 ]. OA is a classic example of joint destruction and osteoproliferative changes influenced by significant risk factors for joint degeneration, such as obesity, malalignment, trauma, or changes in joint loading associated with joint instability [ 10 , 11 , 12 ]. It is an age-related disease, and weight gain in particular causes significant progression of cartilage and meniscal lesions.…”
Section: Introductionmentioning
confidence: 99%